Termination of pregnancy in a border region between Switzerland and Italy (2008–2015) - Reinholz, Danuta; Casati, Simona; Beratta, Ottavio; Marlani, Giorgio (Swiss medical weekly, 2018)
In Switzerland, voluntary termination of pregnancy (VTP) can be performed in all public and private hospitals with an obstetrics/gynaecology department. For various reasons, many Italian women use the Swiss healthcare system, in particular in Canton Ticino, a border region adjacent to Italy in the southern part of Switzerland, when they want to have a VTP. In this study, we aimed to illustrate trends in the VTPs in the Canton Ticino between 2008 and 2015 and demonstrate differences between the Swiss women resident in Switzerland (SSR), foreign women resident in Switzerland (FSR) and foreign women resident abroad (FAR), focusing in particular on the Italian women as during this period there were legal changes in Italy. The number of VTPs was constant on a national level (10,924 in 2008, 10,255 in 2015); in contrast, since 2012 the number has progressively decreased (41%) in Ticino, mainly because of the significant reduction in VTPs in women resident in Italy (decrease of 75.7%). In addition, we wanted to evaluate the impact of the pre-VTP counselling at a family planning centre (FPC) on the VTP decision. The high number of pre-VTP consultations suggests that this service is appreciated and helpful. We observed an encouraging trend in changing the decision to have a VTP after the consultation at the FPC, where 12% of the pregnant women decided to continue the pregnancy. Because of its location, the Canton Ticino is an example how availability of certain drugs, methods and laws can influence the cross-border flow of the patients.